(3TQM GdhbGjIs - (3fXGe GdOjf eMeO Hf YHO GddWja Hf edcs; (3eMehO Hf YHjOGddg Hf EHQGgje GdeMHhHjj GdMfaj , HQgGf GdTQjYI,J (B673 (3g` s ((3CMeO eMeO YjSi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi LYd GdYde CQHM GdeJGLQ cJGH GdWgGQI s
(3BNQgG (B:s
(3jfJgi HcJGH GdNfKi s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3fSNI ebGHdIs
(3cJHJ HBNQgG hUjI HChdgG agQS HGdCHhGH s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
Keywords: (3Gdabg GdMfajs